"Mit szólna Bach, Mozart és Beethoven?": Szülői vélemények a Covid-19 világjárvány miatti lezárásokat követő online hangszeres zeneoktatás hatékonyságáról (Training and Practice : Journal of Educational Sciences, 2024)
In March 2020, the COVID19 pandemic led to a number of fundamental changes in all education systems. Following the lockdowns that aimed at limiting the spread of the virus, educational processes had to be re-thought globally. Countless institutions have started online-based distance education, in many cases despite the lack of the necessary infrastructure background and adequate preparation of teachers. At the time of the data collection of our research, in the spring of 2022, the distance learning form was only used in certain areas, e.g. in the part-time and evening courses of some higher education institutions. In all levels of public education, the previous in-person education has returned, including in the field of music education. Singing and the sound of instruments can be heard from music schools again, and for the outside observer, the old order has been re-stored. However, those who participated in online education must carry their good or not so good memories with them, Children carry on the knowledge they acquired or seemed to have, and teachers and parents mainly carry their experiences. Our previous investigation focused on music teachers and children, and our current research focuses on par-ents who are in the background, but are constantly present, providing reinforcement and help. The aim of our study is to analyse how the parents of children attending music school and playing instruments (N=458) felt about the movement of music education to online platforms, as well as their children’s motivation and academic efficiency. Based on our results, we concluded that the parents accepted and undertook the additional burdens associated with virtual education, and their children could continue their extracurricular studies in a supportive environment. Parents noticed a change in the effectiveness of education, but it was important to them that their children did not interrupt their music studies, so they supported them with their attention even when the chil-dren were less motivated.
Keywords: online music education; Covid19; art education; parental opinions